Aerodynamic Analysis of Diffuser with Airfoil-Based Curved Geometry Across Various Prototypes - Ramadhan, Galang Baruna; Wiratama, I Kade; Joniarta, I Wayan (Journal of Mechanical Engineering, Science, and Innovation, 2025)
The diffuser can increase air velocity in wind turbines by utilizing pressure differences, particularly in small-scale wind turbines. However, some previous research still uses a simple diffuser shape. One alternative diffuser shape is using the airfoil, the wortmann Fx 63-137 airfoil has high lift, exhibits soft stall characteristics, and has excellent overall performance. This study aims to analyze the wind velocity and wind power output generated by an airfoil-based diffuser. Aerodynamic simulations were used with an inlet wind speed of 5.6 m/s. The diffuser has a diameter of 1020 mm, with length to diameter ratios of 0.1, 0.137, 0.221, and 0.371, with angles of attack from 0° to 8° in 2° increments. The results show that the diffuser 0.371 ratio at an 8° angle of attack achieved the highest wind speed of 10.22 m/s, it generate 513 watts. Conversely, the lowest wind speed was observed with a 0.1 ratio at an 8° angle, where the velocity reached 6.58 m/s, producing 137 watts of wind power. Those findings indicate that diffuser length is directly proportional to wind velocity. However, variation in the angle of attack result in maximum wind velocity at specific angles, and wind power output is directly proportional to wind velocity.